2020
DOI: 10.1186/s12961-020-0536-9
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising the initiation of researcher and research user partnerships: a meta-narrative review

Abstract: Background: Integrated knowledge translation refers to researcher and research user partnerships to co-generate and implement knowledge. This type of partnership may be critical to success in increasing knowledge use and impact, but the conceptualisation of its initiation has not been fully developed. Initiating this type of partnership has proven to be challenging but crucial to its success. The purpose of this study was to conduct a meta-narrative review of partnership initiation concepts, processes, enabler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…The majority of clinician participants wanted to be more involved in research studies but were unable to get involved to the extent they would like to. This finding is supported by other research that suggests that clinicians want to undertake research, but the majority do not have protected time and if they do, the opportunity is often lost because of competing clinical demands [11,[28][29][30]. Clinicians in our study were frustrated they were not involved in the development of research studies and are usually first aware of a particular study when they are asked to recruit participants from their caseload.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The majority of clinician participants wanted to be more involved in research studies but were unable to get involved to the extent they would like to. This finding is supported by other research that suggests that clinicians want to undertake research, but the majority do not have protected time and if they do, the opportunity is often lost because of competing clinical demands [11,[28][29][30]. Clinicians in our study were frustrated they were not involved in the development of research studies and are usually first aware of a particular study when they are asked to recruit participants from their caseload.…”
Section: Discussionsupporting
confidence: 63%
“…The views of the clinician participants in our study are similar to those reported in previous studies. A meta narrative review of enablers and barriers of the initiation of research and research user partnerships [11] identified that the personality of the researcher was seen as an enabler to integrated knowledge transfer when perceived as positive and as a barrier when perceived as negative by research users. Attitudes about researchers and the perceived value of research were also identified as being important in enabling or getting in the way of initiating research in health care settings [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To illustrate the volume of studies being produced, there has been a flurry of studies, in the first 2 months of 2020 alone, on the collaboration and coproduction of health research. The titles include 'Building an integrated knowledge translation (IKT) evidence base: colloquium proceedings and research direction' [76], 'Using a 'rich picture' to facilitate systems thinking in research coproduction' [77], 'Exploring the evolution of engagement between academic public health researchers and decision-makers: from initiation to dissolution' [78], 'Research co-design in health: a rapid overview of reviews' [79], and 'Conceptualising the initiation of researcher and research user partnerships: a metanarrative review' [80]. Finally, another article in May 2020 presented a new conceptual model for health research systems to strengthen health inequalities research [81].…”
Section: Whose Literature?mentioning
confidence: 99%
“…Currently, the IKT or research partnership literature describes strategies, barriers and facilitators to research partnerships from the perspective of researchers and knowledge users [ 10 , 11 , 17 – 19 ]. However, little is known about how trainees engage in research partnership approaches such as IKT.…”
Section: Introductionmentioning
confidence: 99%